2009
DOI: 10.1111/j.1461-9563.2009.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant silicon and sugarcane cultivar on mandibular wear in the stalk borer Eldana saccharina

Abstract: 1 Silicon can increase the resistance of plants to attack by herbivorous insects. The present study aimed to determine the effect of silicon and cultivar on mandibular wear in larvae of the sugarcane stalk borer Eldana saccharina Walker (Lepidoptera: Pyralidae). 2 Four sugarcane cultivars, resistant (N21, N33) and susceptible (N11, N26) to E. saccharina were grown in a pot trial in silicon deficient river sand, with (Si + ) and without (Si -) calcium silicate. Individual third-instar larvae were confined on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 37 publications
4
61
0
2
Order By: Relevance
“…A correlation analysis showed that pupal weight, fecundity, net reproductive rate and intrinsic rate of increase were all negatively correlated with Si content in the corn diet, while the duration of larval and pupal stages, longevity of adults and mean generation times were not signifi cantly affected (Horng and Chu 1990 ). Later, several studies also showed that Si fertilization altered survival, reproduction and host plant preferences of chewing (Goussain et al 2002 ;Massey et al 2006 ;Kvedaras et al 2009 ) and sucking insects (Basagli et al 2003 ;Correa et al 2005 ;Korndörfer et al 2011 ). Costa and Moraes ( 2006 ) showed that the application of Si signifi cantly reduced the number of nymphs, the population growth rate, the post-reproductive period and the longevity of the greenbug.…”
Section: Nutritional Defencesmentioning
confidence: 94%
See 3 more Smart Citations
“…A correlation analysis showed that pupal weight, fecundity, net reproductive rate and intrinsic rate of increase were all negatively correlated with Si content in the corn diet, while the duration of larval and pupal stages, longevity of adults and mean generation times were not signifi cantly affected (Horng and Chu 1990 ). Later, several studies also showed that Si fertilization altered survival, reproduction and host plant preferences of chewing (Goussain et al 2002 ;Massey et al 2006 ;Kvedaras et al 2009 ) and sucking insects (Basagli et al 2003 ;Correa et al 2005 ;Korndörfer et al 2011 ). Costa and Moraes ( 2006 ) showed that the application of Si signifi cantly reduced the number of nymphs, the population growth rate, the post-reproductive period and the longevity of the greenbug.…”
Section: Nutritional Defencesmentioning
confidence: 94%
“…It has been widely reported that the hardness of plant parts affected mandibular wear in leaf beetle ( P. versicolora ) (Raupp 1985 ;King et al 1998 ), bee ( M. rotundata ) Schaber et al 1993 ), noctuid lepidopteran larvae ( S. exigua ) (Korth et al 2006 ), weevil ( P. callosus ) (Barnes and Giliomee 1992 ), stalk borer (Kvedaras et al 2009 ) and even in the stylet of a true bug ( D. hesperus ) (Roitberg et al 2005 ). Mandibular wear is often attributed to Si deposited within plant tissues (Kvedaras et al 2009 ).…”
Section: Physical Defencesmentioning
confidence: 97%
See 2 more Smart Citations
“…Since then, many fi eld trials on application of silicate materials to highly weathered entisols, ultisols and oxisols low in soluble Si have resulted in signifi cant responses in both cane and sugar yields in several African countries including Mauritius and South Africa (Bishop 1967 ;Cheong and Halais 1970 ;Du Preez 1970 ;Meyer and Keeping 2001 ). The more recent research on Si in Africa has been mainly focused on the infl uence of Si on the resistance of sugarcane to the stalk borer Eldana saccharina (Keeping and Meyer 2006 ;Smith et al 2007 ;Kvedaras et al 2007Kvedaras et al , 2009see Chap. 10 ).…”
Section: Silicon Research In Africamentioning
confidence: 98%